SCAP Mediated GDF15-Induced Invasion and EMT of Esophageal Cancer - Dong, Gang; Huang, Xiaoquan; Jiang, Siyu; Ni, Liyuan; Ma, Lili; Zhu, Chouwen; Chen, Shiyao (Frontiers in Oncology, 2020)
Background: GDF15 is a potential biomarker for patients with esophageal cancer (EC). However, the mechanistic role of GDF15 in the invasion and metastasis of EC remains poorly understood. Methods: We determined the expression and function of GDF15 in esophageal cancer cells (ESCCs) and in patient tissue samples using western blotting, migration and invasion assays, immunohistochemistry, Co-IP assays, and quantitative real-time-PCR. In addition, a pulmonary metastatic nude mouse model was used to determine the function of GDF15. We then supplemented our experimental results with database analysis to validate our findings. Results: GDF15 was upregulated in EC, and was associated with poor differentiation, high metastasis rates and worse prognosis. GDF15 knock-down reduced the migration and invasion of ESCCs. Co-IP assays demonstrated its association with SCAP, while GDF15 knock-down decreased SCAP levels. SCAP overexpression reversed the migration, invasion and EMT in GDF15-siRNA ESCCs. However, after incubation with β-cyclodextrin (β-CD), the ability of migration and invasion was weakened, EMT was reversed again. Migration, invasion, and EMT were enhanced in GDF15-siRNA ESCCs cultured in the presence of cholesterol and were similar to GDF15-siRNA ESCCs overexpressing SCAP. In vivo, knockdown of GDF15 inhibited lung metastasis of ESCCs and was reversed by SCAP overexpression or high cholesterol diet. Increased lung metastasis after SCAP overexpression was partially suppressed by intraperitoneal injection of β-CD. In addition, we determined that GDF15 was a direct target of miR-1324, miR-1324 was down-regulated in EC tissues. MiR-1324 upregulation resulted in decreased GDF15 expression and metastasis in ESCCs. Conclusions: We demonstrated that SCAP mediated GDF15-induced the invasion and metastasis of EC by regulating cholesterol metabolism. In addition, GDF15 was shown to be a direct target of miR-1324. Keywords: esophageal cancer; metastasis; GDF15; SCAP; miR-1324